Disparities in Access to Revascularization: Evidence from New York - Michael K. Gusmano; Daniel Weisz; Catherine Allende; Victor G. Rodwin (Mary Ann Liebert, 2019)
Purpose: To quantify and compare citywide disparities in the performance of coronary revascularization procedures in New York residents diagnosed with ischemic heart disease (IHD) by the characteristics of the patients and their neighborhood of residence in 2000?2002 and 2011?2013. Methods: We identify the number of hospitalizations for patients with diagnoses of IHD and/or congestive heart failure (CHF) and the number of revascularization procedures performed on the population 45 years and older, relying on hospital administrative data for New York City, by area of residence, from the Statewide Planning and Research Cooperative System (SPARCS). We conduct multiple logistic regressions to analyze the factors associated with revascularization for hospitalized patients admitted with IHD and CHF over the two time periods. Results: Despite any decline in population health status, both the age-adjusted rates of inpatient hospital discharges for acute myocardial infarction, for IHD and for CHF, decreased as did the rates of revascularization procedures. Racial and ethnic disparities were much smaller in the later period than those documented earlier. However, there were persistent gender, insurance status, and neighborhood-level disparities in the treatment of heart disease. Conclusions: With the declines in rates of heart disease, our findings point to the need for more clinical and population-based research to improve the understanding of why race/ethnicity, gender, insurance status, and neighborhood-level disparities persist in the treatment of heart disease.